Study of Shark Kidney Histology (Carcharhinus sorrah) - Darajat, Zakia (Proceeding International Conference on Science and Engineering, 2017)
Shark is a fish widespread in the tropical Indo-Pacific Ocean with a depth of 75 to 130 meters. Shark is a cartilaginous fish (Elasmobranchii). The fish is an ancient animal species that are still alive and also have different characteristics with bony fishes. Research on the histology of the shark’s kidneys is still rare. The purpose of this study was to describe the histology of the shark kidneys (Carcharhinus sorrah). In this study we used one individual shark (Carcharhinus sorrah) from Depok Beach, Yogyakarta. The method used in this research was paraffin method with Hematoxylin-Eosin staining. From microscopic observation, the kidneys consist of glomerular parts, proximal tubules, distal tubules and lymphoid tissue.